High isolation MIMO antenna array for multiband terahertz applications - Youssef Amraoui; Imane Halkhams; Rachid El Alami; Mohammed Ouazzani Jamil; Hassan Qjidaa (Results in Engineering, 2024)
The advancement of future technology seeks to create wireless systems capable of achieving faster data transfer rates. One solution to confront this challenge is by employing Multiple-Input Multiple-Output (MIMO) systems. Nonetheless, the primary obstacle in assessing MIMO performance revolves around the size and spacing of the antennas to maintain isolation among the ports. Consequently, it is essential to devise an approach to tackle these challenges, with the utilization of a DGS as a viable and promising approach. Hence, in this study, we developed a dual-frequency MIMO system featuring two linear array antennas with two elements each and configured to function at 128 GHz and 178 GHz. Initially, this design is conceived as a single-element structure before evolving into a two-element MIMO antenna array configuration. The antenna's physical dimensions are 2.7 × 3.65 × 0.15 mm3, and it consists of two linear array nodes positioned at a separation distance of 0.18 mm. Additionally, the antenna delivers peak gains of 5.16 dB and 6.24 dB at frequencies of 128 GHz and 178 GHz, respectively. The values of various MIMO performance indicators meet stringent standards with ECC values below 0.012 and a DG of approximately 10 dB. Furthermore, the TARC remains below 0 dB. The aim of this research is to create a novel design for a THz antenna that can achieve a wide bandwidth and a high gain while maintaining the standard compact antenna size necessary for THz applications.